UPAYA MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VII C SMPN 4 MADIUN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) - Elisabeth Titi Betan; Vigih Hery Kristanto (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2016)
This research is intended to develop students` activity and achievement in learning, especially for the students of VII C SMPN 4 Madiun by applying Cooperative Think-Talk-Write Model. In this case, learning activity consists of reading (which refers to think), discussing (which refers to talk) and writing (which refers to write). This research applies Classroom Action Research. The subject of this research is the students of the first grade of junior high school (VII C) in SMPN 4, in the school year of 20015/2016. The class population consists of 30 students. The data analysis shows that the percentage of learning activity in Cycle I is 22,22%. Moreover, the analysis proves that: (I) the percentage of learning activity in mathematics in Cycle I is 5,56%. Furthermore, the percentage of learning activity in mathematics in Cycle II increases significantly. Hence it gains 47,62%, however the standard completion in two Cycles has not been achieved yet. In short, the use of Cooperative Think-Talk-Write Model is able to increase the students` learning activity for the students of VII C SMPN 4 Madiun. (2) The class completion rate in Cycle I is 10%, and it gradually increases in Cycle II : 69,23 %. Yet, the standard indicator has not been gained. Therefore, the use of Cooperative Think-Talk-Write Model in this case is unable to increase the students` learning activity, especially in Mathematics. Key Words :Learning Activity, Students` Achievement, Cooperative Think-Talk-Write Model